Impact of a novel oral health promotion program on routine oral hygiene among socioeconomically disadvantaged smokers: results from a randomized semi-pragmatic trial. Issue 2 (12th February 2019) - McClure, Jennifer B; Anderson, Melissa L; Krakauer, Chloe; Blasi, Paula; Bush, Terry; Nelson, Jennifer; Catz, Sheryl L
Abstract: Smokers are at high risk of oral disease and report sub-optimal oral hygiene. Improving smokers' oral hygiene could reduce their future disease risk. The purpose of this study is to assess the effects of a novel, multi-modal oral health promotion program (Oral Health 4 Life; OH4L) targeted to socioeconomically disadvantaged smokers and delivered through state-funded tobacco quitlines. Smokers ( n = 718) were randomized to standard quitline care or standard care plus OH4L. OH4L recipients received a comprehensive behavioral intervention and were advised of the benefits of routine oral hygiene, encouraged to brush and floss daily (for better oral health and to manage cigarette cravings), and provided a toothbrush and floss. Participants were followed for 6 months to assess the intervention effects on routine oral hygiene (brushing and flossing) and changes in motivation and self-efficacy. Data were collected between 2015 and 2017. At 2-month follow-up, OH4L participants were more likely to meet the American Dental Association (ADA) recommendations for brushing twice daily (adjusted RR = 1.15 [1.04, 1.27], p = .006), flossing daily (adjusted RR = 1.20 [1.03, 1.39], p = .02), and for both brushing and flossing (adjusted RR = 1.33 [1.10, 1.61], p = .003). Daily flossing was more likely at 6-month follow-up (adjusted RR = 1.21 [1.04, 1.42], p = .02) among OH4L participants. The change in self-efficacy and motivation for daily flossing from baseline to 2 months was significantly greater among OH4L participants and mediated the intervention effect on flossing at 6 months. Integrating oral hygiene promotion with standard tobacco quitline services improved oral health self-care. Abstract : People who received standard tobacco quitline services plus an integrated oral health promotion program were more likely to meet recommendations for daily brushing and flossing than those receiving standard quitline services alone.